Application of La-ZSM-5 Coated Silicon Carbide Foam Catalyst for Toluene Methylation with Methanol - Debarpita Ghosal; Jayanta Kumar Basu; Sonali Sengupta (Bulletin of Chemical Reaction Engineering & Catalysis, 2015)
The performance of toluene methylation reaction was studied on H-ZSM-5 catalyst modified with La, Ce and Nb at different percentage loading. It was found that 10% metal loading produced the best performance in the reaction in terms of toluene conversion. The catalyst was coated on silicon carbide foam support which showed better conversion than the pelleted catalyst. Again, among the treated and untreated H-ZSM-5, the La-ZSM-5 catalyst is chosen for the reaction for its highest selectivity towards xylene, the main product. All catalysts were characterized in terms of surface properties, SEM, XRD and NH3-TPD. Kinetic study was done on La-ZSM-5 catalyst with 10% loading. In this kineticstudy, Langmuir Hinshelwood kinetic model with surface reaction as rate controlling step was selected as the rate equation. The activation energy was found to be 47 kJ/mol. © 2015 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)